TEACHING COHERENT ORAL SPEECH IN RUSSIAN LANGUAGE LESSONS (British Journal of Global Ecology and Sustainable Development, 2025)
The article discusses methodological aspects of teaching coherent oral speech in Russian language classes. It analyzes key approaches to developing oral skills among students learning Russian as a foreign language, including explanatory and inquiry-based methods, as well as speech imitation techniques. Special attention is given to the relationship between dialogue and monologue speech and their impact on the formation of communicative skills. The importance of combining oral and written speech for effective language acquisition is emphasized. Examples of effective methods, such as the use of visual aids, textbooks, and modern digital technologies, are provided. In conclusion, the article justifies the necessity of a comprehensive approach to teaching Russian to ensure fluency in both professional and everyday communication.